Social Actor Exclusion on 2019 Presidential Election News Reporting in MediaIndonesia.com and iNews.id (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
Mass media, in its reporting, always bring out some social actors. The risen social actors always have influence on the mass media which publish them. It is common to have different news based on the mass media they are from. This study was made in order to find out the representation of social actors in Mediaindonesia.com and iNews.id based on Theo van Leeuwen’s exclusion strategy (suppression and backgrounding). Data sample was collected by observing the social actors’ representation on both media, applying Simak Bebas Libat Cakap (Uninvolved Conversation Observation) technique on online (website/youtube.com) data and taking notes (copy-paste). Based on the analysis conducted during the 2019 presidential and vice presidential candidate pre-appointment period on July 10th to August 8th 2018, it was found out that Joko Widodo was still favored by the public to run for president in 2019, competing with Prabowo Subianto. It was evident from the news frequently published in mediaindonesia.com and iNews.id, either by suppression or backgrounding. Joko Widodo was being backgrounded by mediaindonesia.com by calling him ‘Mantan walikota Solo’, ’mantan Gubernur DKI Jakarta’, or ‘presiden’. On the other side, Prabowo Subiyanto was being backgrounded with ‘Ketua Umum partai Gerindra’, ’mantan Danjen Kopassus’ or ‘mantan pangkostrad’. The forms of backgrounding that appears in the data were in accordance with the experiences of the social actors had as they were serving in particular institutions. It means the journey of the social actors in leading an institution take effect on the backgrounding that is being shown. Meanwhile, in suppression, the ownership of the media is the one giving influence instead. Mediaindonesia.com tended to take sides on Joko Widodo because its owner, Surya Paloh, was going to join coalition with him if he would run for the presidential election. On the other hand, iNews.id tended more to Prabowo Subianto considering the frequencies of the news being shown in the last month. The result of this analysis can give an overview about social actors’ positions in the news..